2002
DOI: 10.1017/s0140525x02000067
|View full text |Cite
|
Sign up to set email alerts
|

The self-organizing consciousness

Abstract: We propose that the isomorphism generally observed between the representations composing our momentary phenomenal experience and the structure of the world is the end-product of a progressive organization that emerges thanks to elementary associative processes that take our conscious representations themselves as the stuff on which they operate, a thesis that we summarize in the concept of Self-Organizing Consciousness (SOC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
1
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(151 citation statements)
references
References 311 publications
(337 reference statements)
9
135
1
6
Order By: Relevance
“…At the extremes, totally implicit knowledge, like procedural knowledge, is completely specific to a given situation, whereas totally explicit knowledge could be transferred to representations in the lexical system-meaning that it could be verbalized (Dienes & Perner, 1999). In a complementary fashion, Perruchet and Vinter (2002) claimed that transfer of knowledge from the original situation (i.e., learning) to another situation (i.e., generation task) is possible only when the elements that are common to both situations (i.e., the task sequence) are conscious. In that sense, the lack of transfer to the generation task in Experiment 2 implies that the gained knowledge was implicit.…”
Section: Discussionmentioning
confidence: 99%
“…At the extremes, totally implicit knowledge, like procedural knowledge, is completely specific to a given situation, whereas totally explicit knowledge could be transferred to representations in the lexical system-meaning that it could be verbalized (Dienes & Perner, 1999). In a complementary fashion, Perruchet and Vinter (2002) claimed that transfer of knowledge from the original situation (i.e., learning) to another situation (i.e., generation task) is possible only when the elements that are common to both situations (i.e., the task sequence) are conscious. In that sense, the lack of transfer to the generation task in Experiment 2 implies that the gained knowledge was implicit.…”
Section: Discussionmentioning
confidence: 99%
“…Given the continual ebb and flow of evidence for and against unconscious perception, one may question whether conclusive results will ever be possible. A very similar controversy has played out in the literature regarding unconscious learning (Dulany, 1997;Perruchet & Vinter, 2002;Shanks & St. John, 1994). Part of the problem may result from the attempt to specify the nature of internal processing from behavioral data (especially for very subtle, complex distinctions, and especially from global indicators such as d′).…”
Section: A Concluding Caveatmentioning
confidence: 98%
“…They concluded that consciousness is epiphenomenal, merely providing the results of processing that has already been carried out to the highest causal levels. If, on the contrary, conscious processes are capable of overriding unconscious influences until the point where d′ ϭ 0, then consciousness appears to have a strong causal role (Dulany, 1997;Perruchet & Vinter, 2002), one that is perhaps stronger than presently recognized. That is, conscious processes are operating below the subjective threshold (cf.…”
Section: Implications For Theories Of Conscious/unconscious Processingmentioning
confidence: 99%
“…First, critical reviews (e.g., Dulany 1997;Perruchet & Vinter 2002;Shanks & St. John 1994) find no defensible evidence for use of unconscious rules in learned categorization. Second, according to a view recently elaborated (e.g., Dulany 1997;Perruchet & Vinter 2002), automatic categorization occurs with direct activation of an awareness of kind from awareness of features or form. With automatization, category representations should drop out, not down to an unconscious level -a view consistent with accumulating evidence for diminishing fMRI activation in relevant networks during automatization (e.g., Schneider et al 2003).…”
Section: Introductionmentioning
confidence: 99%